Optical and magneto-optical properties of thin films for high density information recording - Kravets, V.G.; Poperenko, L.V.; Yurgelevich, I.V.; Petford-Long, A.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
It was found that optical and magneto-optical (MO) properties of thin film materials have potential application for blue laser recording. For this purpose, we have used a combination of ellipsometric and polar MO Kerr effect measurements. The optical and magneto-optical properties of Mn(Sb₁-xBix) and Co-Pt nanocrystalline films were investigated for incident photons in the energy range from 1.3 to 4.0 eV. A large Kerr rotation angle of about 0.570 was observed at photon energy hw»2.65 eV for the Mn₅₅Sb₃₆Bi₉ film with an average grain size of 30 nm. The changes of the exchange splitting and the spin-orbit interaction strength are responsible for the strong dependence of Kerr effect in Mn(Sb₁-xBix) nanocrystalline films. It was shown that the large MO polar Kerr rotation angle is correlated with a perpendicular magnetic anisotropy in nanocrystalline Co₃Pt films